A cerium-cobalt composite oxygen carrier and its preparation method and application

By adopting the preparation method of amphibrium cobalt compound oxygen, the complexing agent and activated carbon are added to the hybrid solution of nitrate nitrate and cobalt nitrate. The chain renovation shows the problem of low reaction activity, low CO selectivity and cycle stability, realize high -reactive activity, good synthetic gas selectivity and cycle stability, and simplify the preparation process.

CN115888737BActive Publication Date: 2025-01-28NORTHWEST UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202211008688.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-08-22
Publication Date
2025-01-28
Estimated Expiration
2042-08-22

AI Technical Summary

Technical Problem

The existing oxygen carriers exhibit low reaction activity, low CO selectivity and cycle stability in methane chemical chain reforming reaction, and the preparation process is complex and time-consuming.

Method used

The preparation method of amplifier cobalt composite oxygen is used to add complexing agents and activated carbon to the hybrid solution of nitrate nitrate and cobalt nitrate. After the steps such as heating, microwave treatment, and high-temperature burn, the CEXCO10-XOΔ type oxygen body is obtained. This method simplifies the preparation process and improves the reaction activity and cycle stability of the oxygen carrier.

Benefits of technology

The high -response activity, good synthetic gas selectivity and cycle stability of the composite oxygen body of the amphobolium cobalt are realized, and the preparation process is simple and the production cycle is short.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115888737B_ABST
    Figure CN115888737B_ABST
Patent Text Reader

Abstract

The present invention discloses a cerium-cobalt composite oxygen carrier and a preparation method and application thereof. The preparation method comprises the following steps: sequentially adding a complexing agent and activated carbon to a mixed solution of cerium nitrate and cobalt nitrate to obtain a mixture; heating the mixture to obtain a precursor solution; subjecting the precursor solution to microwave treatment, subjecting the microwave-treated product to high-temperature calcination treatment to obtain the cerium-cobalt composite oxygen carrier. The method is simple in process and short in production cycle, and the obtained oxygen carrier has rich mesopore content, and the rich mesopores improve the mass transfer efficiency of the material at high temperature, and enhance the reaction activity, CO selectivity and cycle stability of the oxygen carrier.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of oxygen carriers and relates to a cerium-cobalt composite oxygen carrier and a preparation method and application thereof. Background Art

[0002] The theoretical hydrogen-to-carbon ratio of the chemical chain reforming reaction of methane to generate synthesis gas is 2:1, which can be directly used in important chemical production processes such as Fischer-Tropsch synthesis. The principle of this reaction can be divided into two steps: the first step is that in the fuel reactor, methane and oxygen carriers undergo a reduction reaction to generate carbon monoxide and hydrogen; the second step is that in the oxidation reactor, the reduced oxygen carrier reacts with carbon dioxide for oxidation regeneration. The oxygen carrier forms a chain cycle in the two reactors, realizing the production of synthesis gas by the chemical chain reforming reaction of methane. The reforming reaction uses carbon dioxide to oxidize and regenerate the oxygen carrier, which consumes greenhouse gases and is beneficial to environmental protection. At the same time, methane does not come into direct contact with oxygen during the reaction process, avoiding the risk of explosion.

[0003] In chemical chain reforming, oxides play the role of "oxygen carriers", and the selection of oxygen carriers in this cycle is crucial. Generally, oxygen carriers must have the following characteristics: high catalytic activity, excellent sintering resistance, high selectivity, high mechanical strength, high oxygen storage capacity and release rate, low cost, and easy preparation. At present, the most studied are oxides of some metals, such as Fe, Ni, Co, Cu, Ce and Mn, as well as perovskites. Among them, CeO2 has a fluorite cubic structure, Ce 3+ / Ce 4+ The mutual conversion between them makes it show good CO selectivity, but its conversion rate to methane is low and its high temperature stability is poor. Based on the single metal oxygen carrier, the composite metal oxygen carrier can improve and improve the low activity of the single metal oxygen carrier.

[0004] The Chinese patent authorization of CN 106669685 B, "An oxygen carrier, its preparation method and application", discloses an oxygen carrier for chemical chain cycle hydrogen production and its preparation method and application. The preparation method comprises the following steps: (1) NaAlO2, NaOH, silica gel, hexadecyltrimethylammonium bromide (CTAB), isomeric hexadecylamine (CA), tetraethylammonium hydroxide (TEAOH) and water are mixed in a certain proportion to form a gel, and the gel system is subjected to hydrothermal crystallization, drying and roasting to obtain material A; (2) Material A prepared in step (1) is dispersed in distilled water to prepare a suspension, titanium dioxide sol is added to the suspension, and a carrier is obtained after filtering, drying and roasting; (3) Lanthanum and / or cerium, nickel and / or cobalt are loaded on the carrier prepared in step (2) to obtain an oxygen carrier. The preparation process uses a variety of templates, and the preparation process is long, especially the crystallization time is long (crystallization at 430-450K for 72 to 120 hours). The application scenario of this oxygen carrier is hydrogen production, not synthesis gas production.

[0005] The Chinese patent application with publication number CN113135598A discloses "an oxygen carrier for methane chemical chain reforming to produce synthesis gas and its preparation method and application". The oxygen carrier of the invention is composed of Ce4O7 and perovskite structure La x Sr 1-x FeO3 composite, the general formula is Ce4O7-La x Sr 1-x FeO3. It is prepared by the sol-gel method: first, lanthanum nitrate, strontium nitrate, cerium nitrate and iron nitrate are used as precursors and mixed with a complexing agent to form a solution; then, the water is evaporated to remove the transparent sol and transformed into a viscous colloid; after spontaneous combustion, grinding and roasting, a composite metal oxide oxygen carrier is obtained. This oxygen carrier is used in the methane chemical chain reforming reaction to produce synthesis gas, but the oxygen carrier of this invention is composed of two rare earths Ce and La, and alkaline earth metal Sr. The oxygen carrier calcined at high temperature (~1000°C) has good reaction stability only when reacting at 900°C, and the overall energy consumption is relatively high.

[0006] Zeng Liangpeng et al. prepared Ce by traditional hydrothermal method. 1-y Co y O 2-δ (y=0.1~0.4) composite oxide, the methane conversion rate and CO selectivity of this material at 650℃ are both around 60% (Journal of Chemistry in Universities, 2017, 38(01):115-125), and the methane conversion rate and CO selectivity are both poor. Li Bo et al. prepared Ce7Fe3Cu by direct ball milling. 0.5 O δOxygen carrier, performance testing and characterization show that the preparation process of the oxygen carrier is simple and time-saving. The methane conversion rate of the reaction at 850°C is about 75%, and its CO selectivity is about 70% (Natural Gas Chemical Industry (C1 Chemistry and Chemical Engineering), 2019, 44(06): 1-7). The comprehensive performance still needs to be improved. Summary of the invention

[0007] In view of the problems existing in the prior art, the present invention provides a cerium-cobalt composite oxygen carrier and a preparation method and application thereof, so as to prepare an oxygen carrier with high reaction activity, good synthesis gas selectivity and cycle stability and a simple preparation process.

[0008] The present invention is achieved through the following technical solutions:

[0009] A cerium-cobalt composite oxygen carrier, the general formula of the cerium-cobalt composite oxygen carrier is Ce x Co 10-x O δ , 6≤x≤9, 17≤δ≤20.

[0010] Preferably, the mesopore ratio of the cerium-cobalt composite oxygen carrier is 90% to 95%.

[0011] Preferably, the methane conversion rate of the cerium-cobalt composite oxygen carrier is 72% to 94%, and the CO selectivity is 79% to 91%.

[0012] The above-mentioned method for preparing a cerium-cobalt composite oxygen carrier is characterized by comprising the following steps:

[0013] S1: adding a complexing agent and activated carbon to a mixed solution of cerium nitrate and cobalt nitrate in sequence to obtain a mixture;

[0014] S2: heating the mixture to obtain a precursor solution;

[0015] S3: subjecting the precursor solution to microwave treatment, and subjecting the product after microwave treatment to high-temperature calcination treatment to obtain the cerium-cobalt composite oxygen carrier.

[0016] Preferably, the complexing agent is at least one of citric acid, glycine, ethylene glycol and urea; the molar ratio of the complexing agent to the total molar amount of cerium and cobalt is (1-1.2):1.

[0017] Preferably, the added amount of the activated carbon is 5wt% to 20wt%.

[0018] Preferably, the temperature of the heating treatment in step S2 is 60-80° C., and the heating time is 1 h to 1.5 h.

[0019] Preferably, the microwave treatment time in step S3 is 13 min to 20 min, and the microwave power is 500 to 700 W.

[0020] Preferably, the high temperature calcination treatment process is specifically to increase the temperature to 400°C at a heating rate of 1-5°C / min and keep it at that temperature for 0.5-1h, and then continue to increase the temperature to 650-900°C and keep it at that temperature for 3-6h.

[0021] The above-mentioned cerium-cobalt composite oxygen carrier is used in chemical chain methane reforming to produce synthesis gas.

[0022] Compared with the prior art, the present invention has the following beneficial technical effects:

[0023] A preparation method of a cerium-cobalt composite oxygen carrier comprises the following steps: mixing and heating the raw materials, so as to effectively make the cerium-cobalt metal ions and the complexing agent fully chelate, and make the activated carbon fully dispersed in the solution, so as to obtain a precursor solution; then the precursor solution is treated by microwave, and the microwave heating method has the advantage of uniform heating, and avoids local overheating causing the change of the oxygen carrier structure; finally, the precursor material is calcined at high temperature, and finally the oxygen carrier with optimized pore structure is obtained. The obtained composite oxygen carrier is Co doped into the CeO2 lattice, forming a cerium-cobalt solid solution, generating lattice defects, improving the oxygen storage capacity of the oxygen carrier, and the bulk lattice oxygen migration rate matches the methane activation rate well, thereby improving the CO selectivity. At the same time, the addition of activated carbon is related to the enhanced interaction between CeO2 and Co3O4, which makes the contact between the two metal oxides closer, thereby promoting the formation of Ce-Co-O solid solution, thereby enhancing the reducibility of the oxygen carrier. In the preparation process, the heating speed during the microwave treatment is fast, which effectively improves the efficiency of oxygen carrier synthesis. In the later stage of microwave treatment, the complexing agent in the precursor solution is partially decomposed, which plays a certain role in regulating the physical pore structure of the oxygen carrier. At the same time, activated carbon is a good receptor of microwave energy. Microwaves can induce carbon materials to produce plasma, which affects the dispersion of Ce and Co on the surface of the oxygen carrier under the microenvironment. The final high-temperature calcination treatment allows the complexing agent to continue to decompose, realizing the re-regulation of the physical pore structure of the oxygen carrier, and the activated carbon is completely gasified after calcination, realizing the regulation of the physical pore structure of the oxygen carrier in the whole process. The combined use of complexing agent and activated carbon effectively controls the physical pore structure of the oxygen carrier. The oxygen carrier with rich mesopore content is obtained by this method. The rich mesopores improve the mass transfer efficiency of the material at high temperature and enhance the reaction activity and cycle stability of the oxygen carrier. At the same time, the preparation method is simple in process and short in production cycle, avoiding the cumbersome preparation process of multiple metal composite oxygen carriers.

[0024] Furthermore, the molar ratio of the complexing agent to the total amount of cerium and cobalt is (1-1.2):1, which can effectively allow the cerium-cobalt metal ions and the complexing agent to form a geometrically configured complex.

[0025] Furthermore, the addition amount of activated carbon is 5wt% to 20wt%, which can effectively control the mesoporous content of the final oxygen carrier.

[0026] Furthermore, the heating treatment temperature in step S2 is 60-80° C., and the heating time is 1 h-1.5 h, which can effectively allow the cerium-cobalt metal ions to be fully chelated with the complexing agent, and the activated carbon to be fully dispersed in the solution.

[0027] Furthermore, the microwave treatment time is 13 min to 20 min, and the microwave power is 500 to 700 W, which can make the precursor solution fully evaporate, concentrate, foam, decompose, and release a large amount of gas, effectively controlling the mesoporous content of the oxygen carrier.

[0028] The further high-temperature calcination treatment process is specifically to increase the temperature to 400°C at a heating rate of 1 to 5°C / min and keep it warm for 0.5 to 1h, then continue to increase the temperature to 650 to 900°C and keep it warm for 3 to 6h. The temperature is increased twice, which can completely remove the residual carbon-containing substances. The first heating to 400°C can effectively decompose the complexing agent, and the second heating to 650 to 900°C can effectively gasify the activated carbon. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.

[0030] Figure 1 The figure is a schematic flow chart of a method for preparing a cerium-cobalt composite oxygen carrier according to the present invention;

[0031] Figure 2 The XRD diagram of the cerium-cobalt composite oxygen carrier prepared in Examples 1 to 4 of the present invention;

[0032] Figure 3 N2 adsorption-desorption isotherms of the cerium-cobalt composite oxygen carriers prepared in Examples 1 to 4 of the present invention;

[0033] Figure 4 The pore size distribution diagram of the cerium-cobalt composite oxygen carrier prepared in Examples 1 to 4 of the present invention;

[0034] Figure 5XRD comparison diagram of the oxygen carriers prepared in Comparative Examples 1 to 3 of the present invention and the cerium-cobalt composite oxygen carrier prepared in Example 2;

[0035] Figure 6 This is a H2-TPR comparison chart of the oxygen carriers prepared in Comparative Examples 1 to 3 of the present invention and the cerium-cobalt composite oxygen carrier prepared in Example 2;

[0036] Figure 7 It is a comparison diagram of N2 adsorption-desorption isotherms of the oxygen carriers prepared in Comparative Examples 1 to 3 of the present invention and the cerium-cobalt composite oxygen carrier prepared in Example 2;

[0037] Figure 8 This is a comparison diagram of the pore size distribution of the oxygen carriers prepared in Comparative Examples 1 to 3 of the present invention and the cerium-cobalt composite oxygen carrier prepared in Example 2;

[0038] Fig. 9 It is a SEM comparison picture of the oxygen carriers prepared in Comparative Example 1(a), Comparative Example 2(b) and Comparative Example 3(c) of the present invention and the cerium-cobalt composite oxygen carrier prepared in Example 2(d). DETAILED DESCRIPTION

[0039] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definition in this specification shall prevail.

[0040] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any specific theory or mechanism.

[0041] Herein, all features such as values, quantities, contents and concentrations defined in the form of numerical ranges or percentage ranges are for simplicity and convenience only. Accordingly, the description of numerical ranges or percentage ranges should be considered to have included and specifically disclosed all possible secondary ranges and individual values ​​within the range (including integers and fractions).

[0042] In this document, unless otherwise specified, “includes,” “including,” “contains,” “has,” or similar terms cover the meanings of “consisting of” and “mainly consisting of,” for example, “A includes a” covers the meanings of “A includes a and other” and “A only includes a.”

[0043] In this document, in order to make the description concise, not all possible combinations of various technical features in various embodiments or examples are described. Therefore, as long as there is no contradiction in the combination of these technical features, the various technical features in various embodiments or examples can be combined arbitrarily, and all possible combinations should be considered to be within the scope of this specification.

[0044] The present invention provides a method for preparing a cerium-cobalt composite oxygen carrier. Figure 1 As shown, the following steps are included:

[0045] S1: adding a complexing agent and activated carbon to a mixed solution of cerium nitrate and cobalt nitrate in sequence to obtain a mixture; wherein the complexing agent is at least one of citric acid, glycine, ethylene glycol and urea, and the molar ratio of the complexing agent to the total molar amount of cerium and cobalt is (1-1.2):1. The activated carbon is wood activated carbon; the addition amount of the activated carbon is 5wt%-20wt%.

[0046] S2: heating the mixture at 60-80° C. for 1 h to 1.5 h to obtain a precursor solution;

[0047] S3: subjecting the precursor solution to microwave treatment, subjecting the product after microwave treatment to high-temperature calcination treatment, and obtaining the cerium-cobalt composite oxygen carrier. The microwave treatment time is 13 min to 20 min, and the microwave power is 500 to 700 W; the high-temperature calcination treatment process is specifically to increase the temperature to 400°C at a heating rate of 1 to 5°C / min and keep the temperature for 0.5 to 1 h, and then continue to increase the temperature to 650 to 900°C and keep the temperature for 3 to 6 h.

[0048] The general formula of the cerium-cobalt composite oxygen carrier synthesized in the present invention is Ce x Co 10-x O δ , 6≤x≤9, That is, δ=17-20, the mesopore ratio of the cerium-cobalt composite oxygen carrier is 90%-95%, the methane conversion rate is 72%-94%, and the CO selectivity is 79%-91%.

[0049] In one invention, the raw materials are mixed and heated to effectively make the cerium-cobalt metal ions and the complexing agent fully chelate, and the activated carbon is fully dispersed in the solution to obtain a precursor solution, and then the precursor solution is treated by microwave. The microwave heating method has the advantage of uniform heating, avoiding local overheating and causing changes in the structure of the oxygen carrier. Finally, the precursor material is calcined at high temperature to finally obtain an oxygen carrier with optimized pore structure. In the preparation process, the speed of microwave heating is fast, which improves the efficiency of oxygen carrier synthesis. In the later stage of microwave treatment, the complexing agent in the precursor solution is partially decomposed, which plays a certain role in regulating the physical pore structure of the oxygen carrier. At the same time, activated carbon is a good receptor of microwave energy. Microwaves can induce carbon materials to generate plasma, which affects the dispersion degree of Ce and Co on the surface of the oxygen carrier under a microenvironment. During roasting, the complexing agent continues to decompose at about 400°C, realizing the re-regulation of the physical pore structure of the oxygen carrier, and the activated carbon is completely gasified in the later stage of roasting, realizing the regulation of the physical pore structure of the oxygen carrier in the whole process. The combined use of complexing agent and activated carbon effectively controls the physical pore structure of the oxygen carrier. The method obtains an oxygen carrier with rich mesopore content, which improves the mass transfer efficiency of the material at high temperature and enhances the reaction activity and cycle stability of the oxygen carrier. At the same time, the preparation method is simple and has a short production cycle, avoiding the cumbersome preparation process of multiple metal composite oxygen carriers.

[0050] The present invention also discloses the application of oxygen carriers in chemical chain methane reforming to produce synthesis gas, specifically:

[0051] The performance test was carried out on a gas-solid fixed bed at a reaction temperature of 850°C. In the reduction reaction stage, nitrogen as a carrier gas and methane as a reaction gas were introduced, wherein the volume fraction of methane was 5% to 15%. The volume space velocity of methane in the reduction reaction stage was controlled to be 200 to 1500 h-1. -1 During the oxidation reaction stage, carbon dioxide gas is introduced to achieve oxidation regeneration of the oxygen carrier, and the volume space velocity of carbon dioxide during the oxidation reaction stage is controlled to be 200-1500h -1 During the whole process, the outlet gas is monitored in real time by a gas infrared analyzer and the data is recorded.

[0052] In addition, the present invention also uses the following characterization techniques to test and characterize the obtained cerium-cobalt composite oxygen carrier, specifically:

[0053] (1) X-ray diffraction characterization (XRD): XRD was performed on a SmartLab (Rigaku) ​​equipped with Cu Kα radiation (U=40 kV, I=30 mA), with the scanning angle (2θ) set in the range of 5° to 95° and the scanning speed at 10°C / min.

[0054] (2) Cold field emission scanning electron microscopy (SEM) SEM was performed using a SU8020 microscope (manufactured by HITACHI).

[0055] (3) Fully automated surface area and porosity characterization (BET). The structural properties of the samples were determined by nitrogen physical adsorption at liquid nitrogen temperature using a micromechanical device (model ASAP 2460). The surface area and pore size distribution were determined by the Brunauer-Emmett-Teller (BET) and Barrete-Joynere-Halenda (BJH) methods, respectively.

[0056] (4) Programmed temperature reduction characterization (H2-TPR): The H2-TPR experiment was carried out on a BELCAT II instrument produced by Microtrac BEL.

[0057] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.

[0058] The following examples use conventional instruments and equipment in the art. The experimental methods in the following examples where specific conditions are not specified are usually carried out under conventional conditions or under conditions recommended by the manufacturer. The various raw materials used in the following examples are conventional commercial products unless otherwise specified, and their specifications are conventional specifications in the art. In the specification of the present invention and the following examples, unless otherwise specified, "%" means weight percentage, "part" means weight part, and ratio means weight ratio.

[0059] Example 1

[0060] A cerium-cobalt composite oxygen carrier, the preparation method of which is as follows:

[0061] Ce(NO3)3·6H2O and Co(NO3)2·6H2O were dissolved in 100 mL of deionized water at a molar ratio of Ce:Co = 9:1 to prepare a solution. Then 70 wt% of citric acid and 5 wt% of wood activated carbon were added to obtain a mixture. The mixture was heated in a 60°C water bath for 1 h to obtain a precursor 5 wt% CS Ce9Co1O 14 (i.e. the precursor material obtained by adding wood activated carbon), and then placed it in a microwave oven and heated for 15 minutes. After the reaction is completed, the product is taken out of the microwave oven and moved into a muffle furnace, first heated to 400°C for 1 hour, and then continued to heat to 750°C and kept warm for 6 hours to obtain the composite oxygen carrier Ce9Co1O 14 .

[0062] Performance test of oxygen carrier in this embodiment:

[0063] Use an analytical balance to weigh 1.3 g of the oxygen carrier sample prepared above and put it into a quartz tube. Then install the quartz tube into a fixed bed catalytic reaction device and check the air tightness. (1) Pass 95% volume fraction of carrier gas N2 into it, and raise the temperature from room temperature to the set temperature of 850°C at a heating rate of 10°C / min. After reaching the set temperature, pass 5% volume fraction of reaction gas CH4 into the device (with a volume space velocity of 300h / min). -1 ) to carry out the first reaction. (2) After the reaction was carried out for 15 min, the reaction gas was turned off and N2 was continuously introduced. After 5 min, 5% volume fraction of CO2 (with a volume space velocity of 300 h / min) was introduced into the reaction. -1 ) The oxygen carrier is oxidized and regenerated. (3) After the oxygen supplementation is completed, the CO2 gas is turned off, and N2 is purged for 5 minutes, and then CH4 is introduced again for the second reaction. After 15 minutes of reaction, the reaction is stopped. During the whole process, the gas at the reactor outlet is detected in real time by a gas infrared analyzer and the data is recorded. After data analysis and processing, it can be obtained that the conversion rate of CH4 under this condition is 78.7%, the CO selectivity is 79.0%, and the mesoporous ratio of the oxygen carrier is 93.7%.

[0064] The XRD test results of the cerium-cobalt composite oxygen carrier prepared in this example are shown in Figure 2 , N2 adsorption-desorption isotherms are shown in Figure 3 , pore size distribution diagram see Figure 4 .

[0065] Example 2

[0066] A cerium-cobalt composite oxygen carrier, the preparation method of which is as follows:

[0067] The difference from Example 1 is that the amount of wood activated carbon added is 10wt%, so the chemical formula of the precursor obtained is 10wt%CS Ce9Co1O 14 .

[0068] Performance test of the oxygen carrier:

[0069] The performance of the oxygen carrier was tested using the method of Example 1. Under the conditions, the conversion rate of CH4 was 93.9%, the CO selectivity was 90.5%, and the mesoporous ratio of the oxygen carrier was 94.6%.

[0070] The XRD test results of the cerium-cobalt composite oxygen carrier prepared in this example are shown in Figure 2 , N2 adsorption-desorption isotherms are shown in Figure 3 , pore size distribution diagram see Figure 4 , SEM images are shown in Fig. 9 (d).

[0071] Example 3

[0072] A cerium-cobalt composite oxygen carrier, the preparation method of which is as follows:

[0073] The difference from Example 1 is that the amount of wood activated carbon added is 15wt%, so the precursor chemical formula obtained is 15wt%CS Ce9Co1O 14 .

[0074] Performance test of the oxygen carrier:

[0075] The performance of the oxygen carrier was tested using the method of Example 1. Under the conditions, the conversion rate of CH4 was 76.9%, the CO selectivity was 75.8%, and the mesoporous ratio of the oxygen carrier was 91.9%.

[0076] The XRD test results of the cerium-cobalt composite oxygen carrier prepared in this example are shown in Figure 2 , N2 adsorption-desorption isotherms are shown in Figure 3 , pore size distribution diagram see Figure 4 .

[0077] Example 4

[0078] A cerium-cobalt composite oxygen carrier, the preparation method of which is as follows:

[0079] The difference from Example 1 is that the amount of wood activated carbon added is 20wt%, and the precursor chemical formula is 20wt% CSCe9Co1O 14 .

[0080] Performance test of the oxygen carrier:

[0081] The performance of the oxygen carrier was tested using the method of Example 1. Under the conditions, the conversion rate of CH4 was 72.9%, the CO selectivity was 83.0%, and the mesoporous ratio of the oxygen carrier was 91.7%.

[0082] The XRD test results of the cerium-cobalt composite oxygen carrier prepared in this example are shown in Figure 2 , N2 adsorption-desorption isotherms are shown in Figure 3 , pore size distribution diagram see Figure 4 .

[0083] The performance test results, XRD lattice analysis results and BET structure characterization results of the oxygen carrier of the above embodiment are shown in Table 1. δ , with relatively high CH4 conversion and CO selectivity. At the same time, through the XRD data in Table 1 and Figure 2Combined analysis shows that the diffraction peaks at 28.5°, 33.1°, 47.5° and 56.3° correspond to the diffraction of cubic fluorite CeO2 111, 200, 220, 311 crystal planes, respectively. No characteristic peak of Co3O4 was found in the XRD test structure, which indicates that the sample has the same cubic fluorite structure as pure CeO2, and forms a cerium-cobalt solid solution with CeO2, that is, Co 3+ Entering CeO2, cerium and cobalt form a solid solution. Figure 2 It can be seen that the addition of activated carbon does not cause much change in the lattice constant of CeO2. This phenomenon mainly occurs because CeO2 particles can interact with Co 3+ The number of combined lattices is limited. The lower the diffraction peak intensity, the smaller the prepared Ce9Co1O 14 The oxygen carrier has smaller crystals, which are conducive to the diffusion of oxygen in the structure. The cerium-cobalt composite oxygen carrier is effectively prepared by the scheme of the present invention.

[0084] Depend on Figure 3 It can be seen that the cerium-cobalt composite oxygen carrier prepared in Examples 1 to 4 of the present invention is a type IV isotherm with an H3 hysteresis loop, indicating that the sample has a mesoporous structure. It is also found in the figure that the distance between the adsorption / desorption branches is very small, indicating that the sample has open structural pores during the oxidation reaction and the diffusion resistance is very small. The distribution of these pores effectively increases the oxygen transfer rate of the material. At the same time, according to the results of Table 1, when the amount of activated carbon added is 10%wt, the mesopore ratio of the synthesized oxygen carrier is relatively high, and at the same time, the reaction activity of the corresponding oxygen carrier is also relatively high. This is because under the amount of activated carbon added, Co is more evenly dispersed on CeO2, and at the same time, the effective dispersion of an appropriate amount of activated carbon added in the precursor also affects the number and proportion of mesopores.

[0085] Depend on Figure 4 It can be seen that Ce9Co1O 14 The pore size distribution of the oxygen carrier is between 20 and 40 nm, which can make Ce9Co1O 14 The oxygen carrier increases the oxygen transfer rate during use, which is beneficial to the methane conversion rate and stability. The figure also shows that within the range of the wood activated carbon, the synthesized Ce9Co1O 14 The pore size distribution of the oxygen carrier is uniform.

[0086] Table 1 Performance test, XRD lattice analysis and BET structure characterization results of the oxygen carriers prepared in Examples 1 to 4

[0087]

[0088] In addition, the oxygen carrier test method of Example 1 was used to perform 10 performance test cycles on the oxygen carrier prepared in Example 2, and the methane conversion rate and CO selectivity of each cycle are shown in Table 2. As can be seen from Table 2, the methane conversion rate of the sample for 10 cycles was maintained at about 90%, and the CO selectivity was also maintained at a high level. The number of cycles did not significantly affect the methane conversion rate and CO selectivity, proving that the oxygen carrier has good cycle stability. The composite oxygen carrier synthesized in this application has a high mesopore content, and the mesopores effectively improve the oxygen transmission capacity, thereby effectively ensuring the cycle stability of the material.

[0089] Table 2 Results of 10 cycles of performance testing of the oxygen carrier prepared in Example 2

[0090]

[0091] Comparative Example 1

[0092] The difference from Example 1 is that no wood activated carbon is added.

[0093] The performance test process of the oxygen carrier prepared in this comparative example is consistent with the test method of Example 1, specifically:

[0094] Use an analytical balance to weigh 1.3 g of the oxygen carrier sample prepared above and put it into a quartz tube. Then install the quartz tube into a fixed bed catalytic reaction device and check the air tightness. (1) Pass 95% volume fraction of carrier gas N2 into it, and raise the temperature from room temperature to the set temperature of 850°C at a heating rate of 10°C / min. After reaching the set temperature, pass 5% volume fraction of reaction gas CH4 into the device (with a volume space velocity of 300h / min). -1 ) to carry out the first reaction. (2) After the reaction was carried out for 15 min, the reaction gas was turned off and N2 was continuously introduced. After 5 min, 5% volume fraction of CO2 (with a volume space velocity of 300 h / min) was introduced into the reaction. -1 ) Oxidation regeneration of the oxygen carrier. (3) After the oxygen replenishment is completed, the CO2 gas is turned off, and N2 is continued to be purged for 5 minutes, and then CH4 is introduced again for the second reaction. After the reaction lasts for 15 minutes, the reaction is stopped. During the whole process, the gas at the reactor outlet is detected in real time by a gas infrared analyzer and the data is recorded.

[0095] Through data analysis and processing, it can be obtained that the CH4 conversion rate of the material prepared in the comparative example is 98.3%, the CO selectivity is 71.8%, and the mesoporous ratio of the oxygen carrier is 55.3%.

[0096] The XRD test results of the oxygen carrier prepared in this comparative example are shown in Figure 5 , H2-TPR Figure 6 , N2 adsorption-desorption isotherms are shown in Figure 7 , pore size distribution diagram see Figure 8 , SEM images are shown in Fig. 9 (a).

[0097] Comparative Example 2

[0098] The difference from Comparative Example 1 is that only Co(NO3)2·6H2O is added to the raw materials, and Ce(NO3)3·6H2O is not added, that is, the oxygen carrier with the chemical formula Co3O4 is obtained.

[0099] Performance test of the oxygen carrier:

[0100] The performance of the oxygen carrier was tested using the method of Example 1. Under these conditions, the conversion rate of CH4 was 18.5%, the CO selectivity was 53.6%, and the mesopore ratio of the Co3O4 oxygen carrier was 28.6%.

[0101] The XRD test results of the oxygen carrier prepared in this comparative example are shown in Figure 5 , H2-TPR Figure 6 , N2 adsorption-desorption isotherms are shown in Figure 7 , pore size distribution diagram see Figure 8 , SEM images are shown in Fig. 9 (b).

[0102] Comparative Example 3

[0103] The difference from Comparative Example 1 is that only Ce(NO3)3·6H2O is added to the raw materials, and Co(NO3)2·6H2O is not added, that is, the oxygen carrier with the chemical formula CeO2 is obtained.

[0104] Performance test of the oxygen carrier:

[0105] The performance of the oxygen carrier was tested using the method of Example 1. Under this condition, the conversion rate of CH4 was 80.2%, the CO selectivity was 69.0%, and the mesoporous ratio of CeO2 oxygen carrier was 92.3%.

[0106] The XRD test results of the oxygen carrier prepared in this comparative example are shown in Figure 5 , H2-TPR Figure 6 , N2 adsorption-desorption isotherms are shown in Figure 7 , pore size distribution diagram see Figure 8 , SEM images are shown in Fig. 9 (c) In addition, the performance test, XRD lattice analysis and BET structure characterization results of the oxygen carriers prepared in Comparative Examples 1 to 3 are shown in Table 3.

[0107] It can be seen from Table 3 that the methane conversion rates of pure CeO2 oxygen carrier (prepared in Comparative Example 3) and pure Co3O4 (prepared in Comparative Example 2) are not ideal, and the combination of the two can significantly improve the methane conversion rate. Since part of the Co3O4 enters the CeO2 bulk phase to form a Ce-Co-O solid solution, the binary composite oxygen carrier can effectively improve the methane conversion rate of the oxygen carrier after compounding. In addition, from the test results, the addition of wood activated carbon has a slight effect on the methane conversion rate of the composite oxygen carrier, but from the perspective of the entire reaction process, the addition of wood activated carbon greatly improves the CO selectivity of the material, which is beneficial to the generation of synthesis gas. The addition of activated carbon will affect the dispersion of Ce and Co on the surface of the oxygen carrier during microwave treatment, thereby affecting the amount of available oxygen in the microenvironment, avoiding excessive oxidation to produce CO2, and thus improving CO selectivity. At the same time, from the XRD characterization results in Table 5 and Figure 5 It can be seen that pure CeO2 oxygen carrier has strong diffraction peaks at 28.5°, 33.1°, 47.5° and 56.3°, among which the diffraction peak at 28.5° is the strongest, indicating that CeO2 mainly exists in a cubic fluorite structure, while pure Co3O4 has diffraction peaks at 19.0°, 31.3°, 36.8°, 44.8°, 59.4° and 65.3°, among which the diffraction peak at 2θ=36.8° is the strongest, indicating that Co3O4 mainly exists in a hexagonal close-packed cubic spinel structure. Different from single metal oxygen carriers, in cerium-cobalt composite oxygen carriers, the characteristic peaks of CeO2 become stronger and sharper, while the characteristic peak of Co3O4 (2θ=19.0°) disappears, and the remaining characteristic peaks also gradually weaken with the decrease of cobalt content. The reason for this phenomenon is that Ce 4+ The ionic radius of the Co cation is larger than that of the Ce 4+ 、Co 2 + 、Co 3+ The ionic radii of the ions are 0.101nm, 0.082nm, and 0.065nm, respectively. This results in more Ce being generated in the cerium-cobalt composite oxygen carrier as the Co doping concentration decreases. 4+ cation, thereby replacing the Co 2+ and Co 3+ , which makes the characteristic peak of CeO2 sharper. Co is incorporated into the CeO2 lattice to form a cerium-cobalt solid solution, resulting in lattice defects, which improves the oxygen storage capacity of the oxygen carrier. The bulk lattice oxygen migration rate matches the methane activation rate well, which improves the CO selectivity. At the same time, from the XRD characterization results in Table 5, it can be seen that the addition of activated carbon reduces the grain size, which is beneficial to the diffusion of oxygen in the structure and the reduction of oxygen in the lattice of the oxygen carrier. From the BET characterization results in Table 3, it can be seen that the addition of activated carbon also greatly increases the mesoporous ratio of the oxygen carrier and makes the reaction activity higher.

[0108] Depend on Figure 6 It can be seen from the H2-TPR that the reduction peaks of the oxygen carriers move toward lower temperatures after adding activated carbon. This is mainly attributed to the fact that activated carbon enhances the interaction between CeO2 and Co3O4. This effect makes the contact between the two metal oxides closer, thereby promoting the formation of Ce-Co-O solid solution, thereby enhancing the reducibility of the oxygen carrier.

[0109] Depend on Figure 7 It can be seen from the N2 adsorption-desorption isotherms that, except for the Co3O4 oxygen carrier (prepared in Comparative Example 2), the other oxygen carriers all exhibit typical type IV isotherms and H3 hysteresis loops (P / P0>0.4), indicating that the oxygen carriers have a mesoporous structure.

[0110] Depend on Figure 8 The pore size distribution diagram shows that the pure CeO2 prepared in Comparative Example 3 and the Ce9Co1O prepared in Comparative Example 1 without adding activated carbon have δ The positions of the peaks of the composite oxygen carriers prepared in Example 2 and Example 2 are increasing successively, indicating that the pore size of the oxygen carrier is also increasing successively. Therefore, the material after adding activated carbon and composite has a larger pore size, which is beneficial to the release of lattice oxygen of the oxygen carrier and effectively promotes the methane conversion rate and stability of the oxygen carrier.

[0111] Depend on Fig. 9 From the SEM image, it can be seen that the particles of the oxygen carrier prepared in Example 2 are smaller, finer, more evenly dispersed, and have a richer void structure. Such a porous structure helps the reaction gas to penetrate and diffuse into the solid particles, promotes the diffusion of methane in the oxygen carrier particles, and thus obtains a higher reaction efficiency.

[0112] Table 3 Performance test, XRD lattice analysis and BET structure characterization results of the oxygen carriers prepared in Comparative Examples 1 to 3 and Example 2

[0113]

[0114] Example 5

[0115] A method for preparing a cerium-cobalt composite oxygen carrier comprises the following steps:

[0116] S1: citric acid and wood activated carbon are sequentially added to a mixed solution of cerium nitrate and cobalt nitrate to obtain a mixture, wherein the molar ratio of citric acid to the total molar amount of cerium and cobalt is 1:1, and the added amount of wood activated carbon is 5wt%.

[0117] S2: heating the mixture at 60° C. for 1.5 h to obtain a precursor solution;

[0118] S3: placing the above precursor solution in a microwave oven, performing microwave treatment for 13 min at a microwave power of 700 W; heating the product after microwave treatment to 400 ° C at a heating rate of 1 ° C / min and keeping it warm for 0.5 h, and then continuing to heat to 650 ° C and keeping it warm for 3 h to obtain a cerium-cobalt composite oxygen carrier.

[0119] The general formula of the cerium-cobalt composite oxygen carrier obtained in this example is Ce8Co2O 18.7 The mesoporous ratio of the cerium-cobalt composite oxygen carrier is 90%, the methane conversion rate is 72%, and the CO selectivity is 79%.

[0120] Example 6

[0121] A method for preparing a cerium-cobalt composite oxygen carrier comprises the following steps:

[0122] S1: citric acid and wood activated carbon are sequentially added to a mixed solution of cerium nitrate and cobalt nitrate to obtain a mixture, wherein the molar ratio of citric acid to the total molar amount of cerium and cobalt is 1.1:1, and the added amount of wood activated carbon is 8wt%.

[0123] S2: heating the mixture at 65° C. for 1.3 h to obtain a precursor solution;

[0124] S3: placing the above precursor solution in a microwave oven, microwave treatment time is 15min, microwave power is 650W, and microwave treatment is performed; heating the product after microwave treatment to 400℃ at a heating rate of 1.5℃ / min and keeping it warm for 0.8h, and then continuing to heat to 700℃ and keeping it warm for 4h to obtain a cerium-cobalt composite oxygen carrier.

[0125] The general formula of the cerium-cobalt composite oxygen carrier obtained in this example is Ce 7.5 Co 2.2 O 18.3 The mesoporous ratio of the cerium-cobalt composite oxygen carrier is 92.5%, the methane conversion rate is 72.9%, and the CO selectivity is 82.5%.

[0126] Example 7

[0127] A method for preparing a cerium-cobalt composite oxygen carrier comprises the following steps:

[0128] S1: citric acid and wood activated carbon are sequentially added to a mixed solution of cerium nitrate and cobalt nitrate to obtain a mixture, wherein the molar ratio of citric acid to the total molar amount of cerium and cobalt is 1:1, and the added amount of wood activated carbon is 15.5wt%.

[0129] S2: heating the mixture at 75° C. for 1.4 h to obtain a precursor solution;

[0130] S3: placing the above precursor solution in a microwave oven, microwave treatment time is 19min, microwave power is 560W, and microwave treatment is performed; heating the product after microwave treatment to 400°C at a heating rate of 3°C / min and keeping it warm for 1h, and then continuing to heat to 730°C and keeping it warm for 3.5h to obtain a cerium-cobalt composite oxygen carrier.

[0131] The general formula of the cerium-cobalt composite oxygen carrier obtained in this example is Ce7Co3O 18 The mesoporous ratio of the cerium-cobalt composite oxygen carrier is 93%, the methane conversion rate is 80%, and the CO selectivity is 83%.

[0132] Example 8

[0133] A method for preparing a cerium-cobalt composite oxygen carrier comprises the following steps:

[0134] S1: citric acid and wood activated carbon are sequentially added to a mixed solution of cerium nitrate and cobalt nitrate to obtain a mixture, wherein the molar ratio of citric acid to the total molar amount of cerium and cobalt is 1.2:1, and the added amount of wood activated carbon is 10wt%.

[0135] S2: heating the mixture at 70° C. for 1.5 h to obtain a precursor solution;

[0136] S3: placing the above precursor solution in a microwave oven, microwave treatment time is 17min, microwave power is 600W, and microwave treatment is performed; heating the product after microwave treatment to 400℃ at a heating rate of 2.5℃ / min and keeping it warm for 0.8h, and then continuing to heat to 780℃ and keeping it warm for 4h to obtain a cerium-cobalt composite oxygen carrier.

[0137] The general formula of the cerium-cobalt composite oxygen carrier obtained in this example is Ce 6.3 Co 3.7 O 17.5 The mesoporous ratio of the cerium-cobalt composite oxygen carrier is 95%, the methane conversion rate is 85%, and the CO selectivity is 89%.

[0138] Example 9

[0139] A method for preparing a cerium-cobalt composite oxygen carrier comprises the following steps:

[0140] S1: citric acid and wood activated carbon are sequentially added to a mixed solution of cerium nitrate and cobalt nitrate to obtain a mixture, wherein the molar ratio of citric acid to the total molar amount of cerium and cobalt is 1.2:1, and the added amount of wood activated carbon is 15wt%.

[0141] S2: heating the mixture at 75° C. for 1.4 h to obtain a precursor solution;

[0142] S3: placing the above precursor solution in a microwave oven, performing microwave treatment for 19 minutes at a microwave power of 500 W; heating the product after microwave treatment to 400°C at a heating rate of 3.5°C / min and keeping it warm for 1 hour, and then continuing to heat to 810°C and keeping it warm for 3.5 hours to obtain a cerium-cobalt composite oxygen carrier.

[0143] The general formula of the cerium-cobalt composite oxygen carrier obtained in this example is Ce6Co4O 17 The mesoporous ratio of the cerium-cobalt composite oxygen carrier is 95%, the methane conversion rate is 90%, and the CO selectivity is 90%.

[0144] Example 10

[0145] A method for preparing a cerium-cobalt composite oxygen carrier comprises the following steps:

[0146] S1: citric acid and wood activated carbon are sequentially added to a mixed solution of cerium nitrate and cobalt nitrate to obtain a mixture, wherein the molar ratio of citric acid to the total molar amount of cerium and cobalt is 1.2:1, and the added amount of wood activated carbon is 18.5wt%.

[0147] S2: heating the mixture at 80° C. for 1.3 h to obtain a precursor solution;

[0148] S3: placing the above precursor solution in a microwave oven, microwave treatment time is 20min, microwave power is 530W, and microwave treatment is performed; heating the product after microwave treatment to 400°C at a heating rate of 4°C / min and keeping it warm for 1h, and then continuing to heat to 850°C and keeping it warm for 3h to obtain a cerium-cobalt composite oxygen carrier.

[0149] The general formula of the cerium-cobalt composite oxygen carrier obtained in this example is Ce6Co4O 17 The mesoporous ratio of the cerium-cobalt composite oxygen carrier is 95%, the methane conversion rate is 92%, and the CO selectivity is 90%.

[0150] Embodiment 11

[0151] A method for preparing a cerium-cobalt composite oxygen carrier comprises the following steps:

[0152] S1: citric acid and wood activated carbon are sequentially added to a mixed solution of cerium nitrate and cobalt nitrate to obtain a mixture, wherein the molar ratio of citric acid to the total molar amount of cerium and cobalt is 1:1, and the added amount of wood activated carbon is 20wt%.

[0153] S2: heating the mixture at 80° C. for 1.5 h to obtain a precursor solution;

[0154] S3: placing the above precursor solution in a microwave oven, microwave treatment time is 20min, microwave power is 500W, and microwave treatment is performed; heating the product after microwave treatment to 400°C at a heating rate of 5°C / min and keeping it warm for 1h, and then continuing to heat to 900°C and keeping it warm for 3h to obtain a cerium-cobalt composite oxygen carrier.

[0155] The general formula of the cerium-cobalt composite oxygen carrier obtained in this example is Ce 8.5 Co 1.5 O 19 The mesoporous ratio of the cerium-cobalt composite oxygen carrier is 94%, the methane conversion rate is 94%, and the CO selectivity is 80%.

[0156] Example 12

[0157] A method for preparing a cerium-cobalt composite oxygen carrier comprises the following steps:

[0158] S1: citric acid and wood activated carbon are sequentially added to a mixed solution of cerium nitrate and cobalt nitrate to obtain a mixture, wherein the molar ratio of citric acid to the total molar amount of cerium and cobalt is 1:1, and the added amount of wood activated carbon is 20wt%.

[0159] S2: heating the mixture at 80° C. for 1.5 h to obtain a precursor solution;

[0160] S3: placing the above precursor solution in a microwave oven, microwave treatment time is 20min, microwave power is 550W, and microwave treatment is performed; heating the product after microwave treatment to 400°C at a heating rate of 4°C / min and keeping it warm for 0.5h, and then continuing to heat to 850°C and keeping it warm for 4h to obtain a cerium-cobalt composite oxygen carrier.

[0161] The general formula of the cerium-cobalt composite oxygen carrier obtained in this example is Ce 8.9 Co 1.1 O 20 The mesoporous ratio of the cerium-cobalt composite oxygen carrier is 95%, the methane conversion rate is 94%, and the CO selectivity is 84%.

[0162] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

[0163] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A method for preparing a cerium-cobalt composite oxygen carrier, characterized in that: The following steps are involved: S1: adding a complexing agent and activated carbon to a mixed solution of cerium nitrate and cobalt nitrate in sequence to obtain a mixture; S2: heating the mixture to obtain a precursor solution; S3: subjecting the precursor solution to microwave treatment, and subjecting the product after microwave treatment to high-temperature calcination treatment to obtain the cerium-cobalt composite oxygen carrier; The complexing agent is at least one of citric acid, glycine, ethylene glycol and urea; The heating temperature in step S2 is 60-80°C and the heating time is 1h-1.5h; The high temperature calcination treatment process specifically includes heating to 400°C at a heating rate of 1 to 5°C / min and keeping the temperature for 0.5 to 1 hour, and then continuing to heat to 650 to 900°C and keeping the temperature for 3 to 6 hours; The general formula of the cerium-cobalt composite oxygen carrier is Ce x Co 10-x O δ , 6≤x≤9, 17≤δ≤20; The mesopore ratio of the cerium-cobalt composite oxygen carrier is 90% to 95%.

2. The method for preparing a cerium-cobalt composite oxygen carrier according to claim 1, characterized in that: The molar ratio of the complexing agent to the total molar amount of cerium and cobalt is (1-1.2):

1.

3. The method for preparing a cerium-cobalt composite oxygen carrier according to claim 1, characterized in that: It is characterized in that The added amount of the activated carbon is 5wt% to 20wt%.

4. The method for preparing a cerium-cobalt composite oxygen carrier according to claim 1, characterized in that: The microwave treatment time in step S3 is 13 min to 20 min, and the microwave power is 500 to 700 W.

5. The method for preparing a cerium-cobalt composite oxygen carrier according to claim 1, characterized in that: The methane conversion rate of the cerium-cobalt composite oxygen carrier is 72% to 94%, and the CO selectivity is 79% to 91%.

6. Use of the cerium-cobalt composite oxygen carrier prepared by the method for preparing the cerium-cobalt composite oxygen carrier according to any one of claims 1 to 5 in chemical chain methane reforming to produce synthesis gas.

Citation Information

Patent Citations

  • An oxygen carrier, its preparation method and application

    CN106669685B

  • Oxygen carrier for preparing synthesis gas through methane chemical chain reforming as well as preparation method and application of oxygen carrier

    CN113135598A

  • Preparation method of ultra-light mesoporous oxygen carrier for hydrogen production through chemical chain reforming coupled water decomposition

    CN114804213A